Evolution: Searching for the genes that separate species - Phifer-Rixey, Megan (eLife, 2014)
Hybrid mice shed new light on the interactions between regions of the genome that help drive the evolution of new species by reducing the fertility of hybrid males.
Keywords: speciation; reproductive isolation; hybrid zone